Letter Discussing Airspace Case No. 73-WE-10-NR 1973 - Don M. Davis:::::: (1973)
A letter from the Chief of the Airspace and Procedures Branch of the Air Traffic Division discussing the public comments received in regards to different runways including the runway located in the former Oxnard Air Force Base.